The Influence of Dividend Policy, Company Size, and Managerial Ownership on Company Value Mediated by Profitability in Non-Cyclical Consumer Companies Listed on the Indonesia Stock Exchange (BEI) - Wata, Imery; Gularso, Kurnadi (Jurnal Indonesia Sosial Sains, 2023)
The research aims to analyze the effect of dividend policy, company size, and managerial ownership on firm value, as well as analyze the effect of dividend policy, company size, and managerial ownership on profitability in consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This study also aims to analyze the effect of dividend policy, company size, and managerial ownership on company value which is mediated by profitability in consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This study used a purposive sampling method. The data used is secondary data obtained from the Indonesia Stock Exchange for consumer non-cyclicals companies for the 2018-2022 period. This study uses dividend policy, firm size, and managerial ownership as independent variables, firm value as the dependent variable, and profitability as a mediating variable. The analysis was carried out using the panel data regression analysis method using panel data processed with Econometric Views (EViews) Ver 10. The results of this study prove that company size and profitability have a positive effect on firm value. Dividend policy and managerial ownership have no effect on firm value. Dividend policy, firm size, and managerial ownership have no effect on profitability, and profitability is unable to mediate the relationship between dividend policy, firm size, and managerial ownership on firm value.